Correlation of Endometrial Glycodelin Expression and Pregnancy Outcome in Cases with Polycystic Ovary Syndrome Treated with Clomiphene Citrate Plus Metformin: A Controlled Study - Selda Uysal; Ahmet Zeki Isik; Serenat Eris; Seyran Yigit; Yakup Yalcin; Pelin Ozun Ozbay (Obstetrics and Gynecology International)
Objective. The purpose of this study was to evaluate the relationship between clomiphene citrate (CC) plus metformin treatment and endometrial glycodelin expression and to then correlate this relationship with pregnancy outcomes. Material and Methods. A total of 30 patients diagnosed with polycystic ovary syndrome (PCOS) according to the Rotterdam criteria constituted our study group. All had been admitted to the gynecology outpatient clinic between June 1, 2011, and January 1, 2012, for infertility treatment. Our control group consisted of 20 patients admitted for routine Pap smear control. They had no history of infertility and were not using contraceptives and they were actively attempting pregnancy. Midluteal progesterone measurement and pipelle endometrial biopsies were performed with both groups. For PCOS patients, metformin treatment was initiated right after the biopsy and CC was added in the second menstrual cycle. Pipelle endometrial biopsies were repeated. Histological dating and immunohistochemistry for glycodelin were performed by a single pathologist who was blinded to the patients’ clinical data. Result(s). The posttreatment ovulation rate in the study group was 93.3%. No pregnancies were achieved in either group when glycodelin expression was not present, even in the presence of ovulation. When glycodelin expression was high in PCOS group, the pregnancy rate was 60% and all pregnancies ended in live births. In weak expression group, however, three out of four pregnancies ended as early pregnancy losses. Conclusion(s). Endometrial glycodelin expression is an important predictor of pregnancy outcomes in both PCOS and fertile groups.